2012
DOI: 10.1007/978-94-007-2888-2_5
|View full text |Cite
|
Sign up to set email alerts
|

Signaling Through the Extracellular Calcium-Sensing Receptor (CaSR)

Abstract: The extracellular calcium ([Formula: see text])-sensing receptor (CaSR) was the first GPCR identified whose principal physiological ligand is an ion, namely extracellular Ca(2+). It maintains the near constancy of [Formula: see text] that complex organisms require to ensure normal cellular function. A wealth of information has accumulated over the past two decades about the CaSR's structure and function, its role in diseases and CaSR-based therapeutics. This review briefly describes the CaSR and key features o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
91
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(93 citation statements)
references
References 237 publications
2
91
0
Order By: Relevance
“…Calcium and CaSR have been reported to either suppress or promote cancer depending on tumor types (7,24,25), and the aberrance in CaSR function in gastric cancer cells was also evident in the AKT/b-catenin pathway, which was enhanced in gastric cancer cells but suppressed in normal cells. Thus, CaSR activation only stimulated proliferation, growth, migration, and invasion of gastric cancer, but not normal cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Calcium and CaSR have been reported to either suppress or promote cancer depending on tumor types (7,24,25), and the aberrance in CaSR function in gastric cancer cells was also evident in the AKT/b-catenin pathway, which was enhanced in gastric cancer cells but suppressed in normal cells. Thus, CaSR activation only stimulated proliferation, growth, migration, and invasion of gastric cancer, but not normal cells.…”
Section: Discussionmentioning
confidence: 99%
“…CaSR activation stimulates [Ca 2þ ] cyt rise, as well as PI3K/AKT, b-catenin, and MAPK signaling (5,21,23,24), all of which are involved in malignant progression of cancers. Ca 2þ signaling is well recognized to regulate proliferation, migration, epithelial mesenchymal transition (EMT), and malignant transformation (22,26 (29).…”
Section: Discussionmentioning
confidence: 99%
“…The CaSR was first identified in tissues and cells implicated in Ca 2+ homeostasis, including the parathyroid glands and the kidney (Brown et al, 1993;Tfelt-Hansen and Brown, 2005;Chakravarti et al, 2012;Geibel, 2010). Recent observations have demonstrated that the CaSR regulates the expression and distribution of members of the claudin (CLDN) family (Ikari et al, 2008;Gong et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…By sensing minute variations of the extracellular Ca 2+ concentration ([Ca 2+ ] e ) and appropriately modulating the cellular responses to these changes, the CaSR plays an essential role in Ca 2+ homeostasis. Hence, it controls parathyroid hormone (PTH) secretion by the parathyroid glands and modulates Ca 2+ fluxes in the kidney and the bone (Chakravarti et al, 2012;Geibel, 2010). Mutations in the CASR gene have been associated with inherited disorders of divalent mineral homeostasis Hannan et al, 2012).…”
Section: +mentioning
confidence: 99%
“…Underlying mechanisms are not fully understood, but dairy products are rich in calcium and vitamin D. Epidemiological studies and interventional studies have shown similar trends between calcium / vitamin D intake and reduced chronic disease risk [11][12][13]. Calcium and vitamin D are critical to epithelial cell differentiation [23]. Differentiation, in turn, regulates growth (reducing outgrowth of premalignant lesions in organs such as the colon) and promotes barrier formation throughout the upper aerodigestive tract and digestive system (combating chronic inflammation).…”
Section: Appro Poult Dairy and Vet Scimentioning
confidence: 99%